Model Pengembangan Kurikulum Pendidikan Bahasa Arab - Abd. Rahman, Anwar; Adhriana, A. Razna Aula; Yotmanisafitri; Nurhikmah; Matta, Andi Nurfadillah; Muaqilah, Husnul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The background of this study is based on the urgent need for a curriculum that is more relevant, flexible, and responsive to modern pedagogical developments, including the demands of communicative competence, technology integration, and the diversity of learner needs. This study aims to analyze classical and contemporary curriculum development models that have been applied in language education, such as the Tyler, Taba, Oliva, Beauchamp, Wheeler, Audrey & Nicholls models, as well as competency-based curricula. The research method uses a literature study by reviewing primary and secondary literature related to curriculum development theory and practice. The data collection method used is literature documentation and in-depth analysis to produce a theoretical conclusion regarding the most effective curriculum model. The results of the study indicate that no single model can be used universally in Arabic Language Education. Effective curriculum development must integrate clarity of objectives, relevant material structure, a communicative approach, and continuous competency-based evaluation. This study emphasizes the importance of an adaptive curriculum, namely a curriculum that combines the best elements of various models according to the characteristics of the institution, learning culture, and learner needs.